Struktur Modal Memediasi Pengaruh Struktur Aset, Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan (Perusahaan non Bank yang Tercatat dalam Indeks LQ45) - Jusmawati Jusmawati; Murni Sari (Jurnal Ekonomi & Bisnis, 2022)
The aims of this research are: 1). To examine the role of capital structure in mediating asset structure, firm size and profitability to firm value. 2) To examine the direct influence between asset structure, firm size, profitability and capital structure on firm value. 3) to examine the direct influence between asset structure, firm size and profitability on capital structure.  The research design used is quantitative research. The data used is secondary data in the form of data based on time series. Data analysis using Smart PLS software version 3.0. The results showed that: 1). Capital structure plays a role in mediating the influence, both the relationship between asset structure and firm size, on firm value. On the other hand, capital structure does not play a role in mediating profitability to firm value. 2) Directly, asset structure and firm size have no significant effect on firm value. However, directly profitability and capital structure have a significant effect on firm value. 3) In addition, asset structure and firm size directly have a significant effect on capital structure. On the other hand, profitability has no significant effect on capital structure